Noise temperature theory and applications for deep space communications antenna systems - Otoshi, Tom Y. (Artech House antennas and propagation library., 2008)
"Deep space communications technology is bringing home benefits to all types of microwave communications systems. This groundbreaking resource explains the breakthroughs that the NASA JPL Deep Space Antenna Network achieved in reducing noise and signal interference. The book focuses on ground-based receivers and how they can be improved to pick up weak or disrupted signals. Practicing microwave engineers in all fields can apply these theories and methods to improve systems performance. In particular, engineers working on deep-space antenna systems can make the most of the techniques for analyzing errors caused by noise temperature. The book explains how to confidently predict receiver noise temperature thereby boosting the capability to receive data. Tutorials, practical formulas, and powerful techniques earn this book a permanent place on every microwave and antenna engineer's desk."--